Cold Injuries in Contemporary Conflict. Issue 3 (1st September 2012) - Mitchell, J; Simpson, R; Whitaker, John
Abstract : Objectives: To describe the cases of cold injury sustained during the most recent winter operational tour of Afghanistan, Op HERRICK 15. Methods: Retrospective review of all notified British military cases of cold injury sustained between 1 Oct 11 and 30 Mar 12 recorded by UK Medical Group Environmental Health Team. Results: 14 patients with 13 Non-freezing Cold Injuries (NFCI) and two hypothermic injuries were identified. Five patients were of African ethnic decent. Eight out of 13 NFCI patients had probably suffered a previous injury, injuries were sustained from December until February and 9/13 NFCI patients had periods of static duties implicated in the injury mechanism. Eight patients were able to remain in operational theatre on restricted duties whilst 6/14 were evacuated home after sustaining their injuries. Conclusions: Although awareness and equipment have improved, cold injuries remain an important cause of Disease and Non Battle Injury on current operations within the British Military. Cases of cold injury are probably under reported and often stem from situations where risk would seem predicable. It is hoped this article will assist in enabling greater understanding of contemporary operational cold injuries and continuing the development of preventative strategies.